2018
DOI: 10.1002/mbo3.728
|View full text |Cite
|
Sign up to set email alerts
|

Efficiently activated ε‐poly‐L‐lysine production by multiple antibiotic‐resistance mutations and acidic pH shock optimization in Streptomyces albulus

Abstract: ε‐Poly‐L‐lysine (ε‐PL) is a food additive produced by Streptomyces and is widely used in many countries. Working with Streptomyces albulus FEEL‐1, we established a method to activate ε‐PL synthesis by successive introduction of multiple antibiotic‐resistance mutations. Sextuple mutant R6 was finally developed by screening for resistance to six antibiotics and produced 4.41 g/L of ε‐PL in a shake flask, which is 2.75‐fold higher than the level produced by the parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Currently, increasing numbers of ε-PL-producing strains have been screened out as the development of novel screening methods. Efforts in ε-PL biomanufacturing research have mainly focused on Streptomyces , especially on S. albulus , which gives the highest reported ε-PL production (70 g/L) in liquid fermentation after strain evolution and fermentation process optimization ( Wang et al, 2019 ). Some other actinomycetes, such as Kitasatospora , Streptomyces ahygroscopicus , Streptomyces griseofuscus and Streptomyces diastatochromogenes have also been investigated in some studies, with various degrees of success ( Ouyang et al, 2006 ; Chen J. et al, 2019 ; Shu et al, 2019; Wang et al, 2021 ).…”
Section: Biosynthesis Of ε-Pl By Various Microorganismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, increasing numbers of ε-PL-producing strains have been screened out as the development of novel screening methods. Efforts in ε-PL biomanufacturing research have mainly focused on Streptomyces , especially on S. albulus , which gives the highest reported ε-PL production (70 g/L) in liquid fermentation after strain evolution and fermentation process optimization ( Wang et al, 2019 ). Some other actinomycetes, such as Kitasatospora , Streptomyces ahygroscopicus , Streptomyces griseofuscus and Streptomyces diastatochromogenes have also been investigated in some studies, with various degrees of success ( Ouyang et al, 2006 ; Chen J. et al, 2019 ; Shu et al, 2019; Wang et al, 2021 ).…”
Section: Biosynthesis Of ε-Pl By Various Microorganismsmentioning
confidence: 99%
“…It has been reported that the introduction of resistance to some macrolide antibiotics can strongly activate the production of various secondary metabolites, including actinorhodin and salinomycin ( Ochi, 2007 ; Zhang et al, 2019 ). Through this technique, mutations conferring resistance to streptomycin and five other antibiotics were successively induced in S. albulus to generate the S. albulus R6 mutant strain, which exhibited the highest reported ɛ-PL production of 70.3 g/L, 2.79-fold greater than the original strain, using an optimized acidic pH shock strategy ( Wang et al, 2019 ). Mutations in protein S12 (Q856H) and RNA polymerase (R99P) of the R6 strain could be responsible for the increased transcription of the pls gene and elevated activities of key enzymes in ɛ-PL biosynthetic pathway, consequently increasing the level of Pls activity, as well as L-lysine and ATP concentrations available for ɛ-PL production ( Wang et al, 2019 ).…”
Section: Strain Improvementmentioning
confidence: 99%
See 1 more Smart Citation
“…However, limitations, such as small-scale and complicated polymerization processes, hinder the extensive use of chemically synthesized EPL. EPL, as a natural existing product, its production mainly relies on biosynthesis with few kinds of microorganisms, such as Streptomycetaceae, Kitasatospora sp ., and Ergot fungi (Shukla et al, 2012 ; Wang et al, 2019 ). Furthermore, the process of commercially producing EPL especially relies on Streptomyces albulus fermentation ( Figure 2 ) as the metabolic process of this microbe combating acid stress (Wang C. Y. et al, 2020 ).…”
Section: ε -Poly-l-lysinementioning
confidence: 99%
“…The former additives could be astaxanthin, which works as an antioxidant to reduce intracellular oxidant response and downregulated relevant gene transcription (Li S. et al, 2020 ), while the latter pointing to replacing the carbon sources to cyclodextrins and glycerol for producing low-molecular-weight EPL, which exhibits more powerful antimicrobial activity than its larger counterparts (Chen et al, 2018 ); (ii) optimizing the producing strategies by combining other computation methodologies. For example, researchers used artificial neural network modeling and surface response methodology to assist to the optimization of the medium composition then enlarging the yield (Bhattacharya et al, 2017 ; Guo et al, 2018 ); or (iii) cloning or mutating the key genes of those microorganism, activating a larger production of EPL (Liu et al, 2019 ; Wang et al, 2019 ; Xu et al, 2019 ). Furthermore, with a more precise production or synthesis mechanism, such as determining the opposite and negative elements that may influence the production, higher yield with a more time-saving and effective production process could be achieved, which could be the preferred pathway for further studies.…”
Section: ε -Poly-l-lysinementioning
confidence: 99%